An Analysis of Performance of Forest Concessionaires in Cambodia - Sovanny, Chhum (2001)
The aim of this study was to highlight the forest management performance of forest concessionaires in Cambodia and to observe how concessionaires' characteristics influence their performance. Data and information were obtained mainly from the study on "Cambodia Forest Concession Review" supported by the Asian Development Bank (ADB). Data used in this study were background information on existing concessionaires, infonnation charges against concessions and sustainable forest management rating of concessionaires. Cross tabulation analysis was carried out to observe the variation in the performance of the concessionaires relating to legal compliance of charges with existing forest law and regulations and forest management performance of concession based on internationally recognized principles of sustainable forest management. The results showed that 70% of the 20 concessionaires have committed illegal activities. About 90% among 10 concessionaires scored poorly in the sustainable forest management rating. The results of the analysis showed that foreign companies, those in the large concession area and higher capital investment have done more illegal activities. In terms of Sustainable Forest Management performance, foreign companies with higher capital investment performed better. It is recommended that the Royal Government of Cambodia should take the appropriate and prompt measures to monitor the performance of concessionaires and should improve its forest concession allocation policy in order to manage forest sustainably in Cambodia.